Smartwatches are more distracting than mobile phones while driving: Results from an experimental study. (January 2021) - Brodeur, Mathieu; Ruer, Perrine; Léger, Pierre-Majorique; Sénécal, Sylvain
Highlights: Smartwatch use has a detrimental effect on driving. Smartwatch vs. Smartphone vs. Vocal Assistant use were compared while driving. Gaze distribution was less focused on the task with a smartwatch than a smartphone. A vocal assistant is the best way to send and receive notifications. Abstract: The use of smartwatches raises a number of questions about their potential for distraction in situations where sustained attention is paramount, like driving a motor vehicle. Our research examines distraction caused by smartwatch use in comparison to mobile phone use while driving. It also studies the difference in distractions caused by inbound text messages versus inbound voice messages, and outbound replies through text messages versus outbound voice replies. A within-subject experiment was conducted in a driving simulator where 31 participants received and answered text messages under four conditions: they received notifications (1) on a mobile phone, (2) on a smartwatch, and (3) on a speaker, and then responded orally to these messages. They also (4) received messages in a "texting" condition where they had to reply through text to the notifications. Eye tracking gaze distribution results show that participants were more distracted in the smartwatch condition than in the mobile phone condition, they were less distracted in the speaker condition than in the phone condition, and they were more distracted in the texting condition than in any of the others. The participants' driving performance remained the same in all conditions except in the texting condition, wherein it became worse. Eye tracking and pupillometry results suggest that participants' mental workload might be lower in the texting condition than in the other three conditions, although this result might be caused by a higher number of glances at the device in that condition. This study contributes to a better understanding of the distraction potential of smartwatches as well as identifying vocal assistants as the least distracting way of communicating while driving a vehicle. Industry leaders could become a key factor in informing the public of the smartwatch's potential for distraction.